2019
DOI: 10.1002/1873-3468.13621
|View full text |Cite
|
Sign up to set email alerts
|

Induction of human hemogenesis in adult fibroblasts by defined factors and hematopoietic coculture

Abstract: Transcription factor (TF)‐based reprogramming of somatic tissues holds great promise for regenerative medicine. Previously, we demonstrated that the TFs GATA2, GFI1B, and FOS convert mouse and human fibroblasts to hemogenic endothelial‐like precursors that generate hematopoietic stem progenitor (HSPC)‐like cells over time. This conversion is lacking in robustness both in yield and biological function. Herein, we show that inclusion of GFI1 to the reprogramming cocktail significantly expands the HSPC‐like popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 103 publications
1
13
0
Order By: Relevance
“…Importantly, generation of engraftable HSCs from fibroblasts was achieved by forcing transient expression of GFI1B in combination with GATA2 and FOS, either with or without ETV6, using pools of doxycycline-inducible lentiviruses (Pereira et al, 2013;Gomes et al, 2018). The efficiency of this approach was even further improved by adding GFI1 into the cocktail, allowing the generation of a similar number of hematopoietic stem-progenitor cells with short-term engraftable capacity in much shorter time, although long-term engraftment capacity was not assessed in this experiment ( Figure 3C; Daniel et al, 2019). How GFI1/GFI1B forced transient expression contributes to the improvement of hemogenic conversion remains to be fully uncovered, but seems to be due to the capacity of at least GFI1B to directly cooperate with GATA2 by co-occupying promoters of critical non-hematopoietic genes leading to their silencing (Gomes et al, 2018).…”
Section: In Vitro Hematopoietic Transdifferentiation From Ips/es Cellmentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, generation of engraftable HSCs from fibroblasts was achieved by forcing transient expression of GFI1B in combination with GATA2 and FOS, either with or without ETV6, using pools of doxycycline-inducible lentiviruses (Pereira et al, 2013;Gomes et al, 2018). The efficiency of this approach was even further improved by adding GFI1 into the cocktail, allowing the generation of a similar number of hematopoietic stem-progenitor cells with short-term engraftable capacity in much shorter time, although long-term engraftment capacity was not assessed in this experiment ( Figure 3C; Daniel et al, 2019). How GFI1/GFI1B forced transient expression contributes to the improvement of hemogenic conversion remains to be fully uncovered, but seems to be due to the capacity of at least GFI1B to directly cooperate with GATA2 by co-occupying promoters of critical non-hematopoietic genes leading to their silencing (Gomes et al, 2018).…”
Section: In Vitro Hematopoietic Transdifferentiation From Ips/es Cellmentioning
confidence: 96%
“…Indeed, such a de-differentiation of hematopoietic progenitor cells has been achieved through combined overexpression of defined sets of transcription factors in both myeloid and lymphoid committed progenitors (Riddell et al, 2014). Conversion of endothelial cells into HSCs is also a natural approach as HSCs arise from HE cells and several protocols are already established for this, most of which use doxycycline-inducible transient overexpression of either GFI1 or GFI1B simultaneously with the overexpression of other factors such as GATA2, FOS, RUNX1, and SPI1 using lentiviral expression vectors ( Figure 3B; Sandler et al, 2014;Lis et al, 2017;Barcia Duran et al, 2018;Daniel et al, 2019).…”
Section: In Vitro Hematopoietic Transdifferentiation From Ips/es Cellmentioning
confidence: 99%
“…Integrating RNA-seq and ChIP-seq analyses, the investigators observed that GATA2 and GFI1B cooperate at the chromatin level, where the AP-1 motif appeared as the most enriched target. Yet another improvement to this method is published in this issue of FEBS Letters [17]. This time, addition of GFI1 to the TF cocktail and coculture of the transduced fibroblasts with a stromal cell line of mouse origin increased the yield of reprogramming even further.…”
Section: Direct Conversion Of Somatic Cells To Haematopoietic Stem Anmentioning
confidence: 99%
“…In this Special Issue of FEBS Letters entitled 'Neural and Hematopoietic Stem Cell Reprogramming', we present a collection of peer-reviewed original articles and reviews authored by select international experts. They discuss the most exciting recent developments in the field, focusing on hematopoietic [1][2][3][4][5] and neural [6][7][8][9][10] (stem) cell generation/reprogramming in vitro. The future research directions and the obstacles ahead are also put into perspective.…”
mentioning
confidence: 99%
“…In short, Chen et al [1] discuss the recent progress in blood cell reprogramming and the potential use of these cells for disease modeling and therapeutic development; Dur an et al [2] compare and discuss the reprogramming methods used to generate hematopoietic stem and progenitor cells; Daniel et al [3] describe an improved human hemogenic induction protocol for establishing an in vitro model of human hematopoiesis, which may facilitate disease modeling and provide a basis for a platform for cell-based therapeutics; Hansen et al [4] discuss the derivation of erythroid, megakaryoid, and myeloid cells from iPSCs and the obstacles currently hindering therapeutic use; Menegatti et al [5] review the complex transcriptional network regulating blood cell generation during embryonic development and how this information can help in generating these cells in vitro; Traxler et al [6] report the most recent advances in direct induced neural (iN) conversion and compare this to other reprogramming-based neural cell models; Greiner et al [7] highlight the implications of sex-related intrinsic mechanisms and different adult stem cell populations (e.g., mesoderm-derived stem cells, neural stem cells, neural crest-derived stem cells) for stem cell differentiation and regeneration and for the design of new treatment options; Erharter et al [8] discuss different approaches to generate induced neural stem cells (iNSCs) and their promising use for disease modeling, autologous cell therapy, and personalized medicine; Birtele et al [9] report that adding neuronal-specific microRNAs into different culture media improves neuronal maturation and the acquisition of electrophysiological properties during direct neural reprogramming; and finally, Denoth-Lippuner and Jessberger [10] take a broader perspective discussing how reprogramming might lead to the rejuvenation of a cell, an organ, or even the whole organism.…”
mentioning
confidence: 99%